MODEL PERSEDIAAN ECONOMIC ORDER QUANTITY DENGAN PENUNDAAN WAKTU PEMBAYARAN DAN MEMPERTIMBANGKAN FAKTOR KERUSAKAN BARANG (STUDI KASUS PADA UD. ALAM SEJAHTERA SEMARANG) - Inge Tara Natika (Jurnal Matematika, 2015)
ABSTRAK. Economic Order Quantity inventory model is a model that is widely used as a decision making tool for inventory control. EOQ model is used to find the optimal order quantity to minimize total inventory costs. This undergraduated thesis is about  Economic Order Quantity inventory model for deteriorating items that affecting to quality and product sale value, the constant demand rate without shortages in inventory, with permissible delay in payments. There are three cases in this inventory model. First, when permissible delay of payments period is less than the replenishment cycle period. Second, when permissible delay of payments period is greater than the replenishment cycle period. And third, when permissible delay of payments period equal to the replenishment cycle period.  Kata Kunci: Inventory, Economic Order Quantity model, delay in payments, deteriorating items.